An Evaluation of Collection Development and Reader's Services at IIT Library, Bombay - Singh, S.P. (DESIDOC Journal of Library & Information Technology, 2003)
Mentions briefly about the establishment of Indian Institute of Technology (IIT), Bombay and ‘its library. Desecrates the methodology used for gathering information, Discusses the acquisition, use and adequacy of library collection. Examines user awareness about various library services and their usefulness. Provides users' and librarian's suggestions about collection and services. http://dx.doi.org/10.14429/dbit.19.4.3493